A labelling operator and relational operations - Huy, Nguyen Xuan (Journal of Computer Science and Cybernetics, 2015)
A set of algorithms of relational operations in the realization of DBMS is described. A quantitative efficiency of these algorithms by using of labeling operator is derived.